EFEKTIFITAS MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DI KELAS VIII SMP NEGERI 1 PINANGSORI - desi ratna sari sigalingging (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe the effectiveness of using reciprocal teaching learning model on students’ mathematical concept of understanding ability at the eighth grade students of SMP Negeri 1 Pinangsori. The research was conducted by using experimental (pretest post test one group design) method with 31 students as the sample and they were taken by using cluster random sampling technique from 119 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using reciprocal teaching learning model was 3.75 (very good category) and b) the average students’ mathematical concept of understanding ability before using reciprocal teaching learning model was 46.74 (fair category) and after using reciprocal teaching learning model was 83.90 (very good category). Furthermore by using inferential statistic (Pair Sample ttest), it could be found significant value was less than 0.05 (0.000 <0.05). It means, there is a significant difference of students’ mathematical concept of understanding ability before and using reciprocal teaching learning model at the eighth grade students of SMP Negeri 1 Pinangsori.